On several species of Oswaldella Stechow, 1919 (Cnidaria, Hydrozoa), including the description of a new species - Cantero, A.l. Peña; Molinero, A. González (Zootaxa, 2018)
Oswaldella is the most speciose genus of Antarctic hydroids, being one of the most characteristic genera of hydrozoans of the Antarctic benthic marine ecosystem. A relatively high number of taxonomic characters allow species identification, but some key ones are difficult to study properly with a light microscope. In order to improve knowledge of species of the genus, a SEM survey of five of the 27 known nominal species of Oswaldella was carried out, including type material of O. grandis and O. terranovae. The study has revealed no significant differences between O. stepanjantsae and O. terranovae and, consequently, the former is considered a junior synonym of the latter. The type material of O. terranovae included material of an unnoticed, unknown species, which is described as O. occulta sp. nov.